Immune checkpoint inhibitors: recent progress and potential biomarkers - Pramod Darvin; Salman M. Toor; Varun Sasidharan Nair; Eyad Elkord (Experimental and Molecular Medicine, 2018)
Cancer immunotherapy: Markers of success Biomarkers that predict a patient’s response to cancer immunotherapy are being developed, and may allow individual tailoring of therapies. Cancer cells can suppress the immune system by activating immune checkpoints, signals that stop the immune system from attacking the host. Immunotherapy, a recently developed treatment, inactivates immune checkpoints, restoring the patient’s immune response against the tumor. Although promising, immunotherapy has a low response rate, and sometimes triggers severe auto-immune reactions. Eyad Elkord at Qatar Biomedical Research Institute in Qatar and coworkers have reviewed biomarkers that could be used to predict individual effects of immunotherapy, identifying nonresponders and preventing adverse immune reactions. They discuss markers based on factors such as immune response level and individual tumor genetics, among others. With further research and testing, these biomarkers could improve the efficacy of this promising new cancer therapy.